2011
DOI: 10.1159/000324561
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Polymorphism and the Progression of Diabetic Nephropathy in Type 2 Diabetes

Abstract: Background/Aims: Three different apo E alleles (E2, E3 and E4) produce apo E isoproteins, which regulate the metabolism of lipoproteins. This study investigated the apo E polymorphisms as a prognostic factor for the development of diabetic nephropathy (DN). Methods: A total of 525 type 2 diabetic patients were enrolled to participate in this prospective observational study. Apo E gene polymorphisms were analyzed by polymerase chain reaction. The progression of DN was defined as a shift to a higher stage of DN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…All statistical analyses were performed with STATA Statistical Package (version 10.0) and were 2 sided, with a significance level of P < 0.05. [14,24,31]. Three sub-studies from one paper about PPARγ rs1801282 C>G polymorphism and 10 sub-studies from two articles about ACACB polymorphism were treated as separate studies in our analyses given that the study bases were sampled from different geographical locations or belonged to different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All statistical analyses were performed with STATA Statistical Package (version 10.0) and were 2 sided, with a significance level of P < 0.05. [14,24,31]. Three sub-studies from one paper about PPARγ rs1801282 C>G polymorphism and 10 sub-studies from two articles about ACACB polymorphism were treated as separate studies in our analyses given that the study bases were sampled from different geographical locations or belonged to different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty publications were carried out in Asians [2-4, 6, 8-10, 13, 14, 19, 22, 26, 31, 34, 36-38, 42-44], 12 in Caucasians [12,17,18,20,21,23,32,33,35,[39][40][41], and 1 in mixed populations [11]. Ten studies reported on microalbuminuria [10,12,14,19,21,22,35,37,40,41], seven reported on macroalbuminuria [6,14,17,19,21,37,41], whereas only three studies were about ESRD [25]. Examining genotype frequencies in the controls, significant deviation from HWE was detected in the four studies [3,4,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some follow-up studies have reported no association between the e2 allele and DN progression [24,25]. However, we need to interpret the results of these studies carefully.…”
Section: Follow-up Studymentioning
confidence: 94%
“…This study analyzed only 169 diabetic patients with normoalbuminuria at the 4-year follow-up, which may lack the power to detect the significance of the e2 allele. In addition, Tien et al [25] investigated 525 patients with type 2 diabetes in a prospective observational study with a median follow-up of 42.4 months. However, this study included diabetic patients with overt proteinuria, and DN progression in those with overt proteinuria was defined as the doubling of serum creatinine instead of the shift to the higher stage of albuminuria that is used in those with normoalbuminuria and microalbuminuria.…”
Section: Follow-up Studymentioning
confidence: 99%